2023
DOI: 10.3171/2022.7.spine22498
|View full text |Cite
|
Sign up to set email alerts
|

How common is acute pelvic fixation failure after adult spine surgery? A single-center study of 358 patients

Abstract: OBJECTIVE There is a paucity of literature on pelvic fixation failure after adult spine surgery in the early postoperative period. The purpose of this study was to determine the incidence of acute pelvic fixation failure in a large single-center study and to describe the lessons learned. METHODS The authors performed a retrospective review of adult (≥ 18 years old) patients who underwent spinal fusion with pelvic fixation (iliac, S2-alar-iliac [S2AI] screws) at a single academic medical center between 2015 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although SPF indeed reinforces the construct stiffness, 12.0%–46.9% of implant failure rate has been reported by previous studies ( Park et al, 2021b ; Gao et al, 2021 ). To reduce the incidence of mechanical complications, multiple pelvic screws or multirod construct have been applied as an advanced SPF technique ( Uotani et al, 2021 ; Lee et al, 2022a ; Lee et al, 2022b ; Tang et al, 2022 ). The current study revealed that both multiple pelvic screws and multirod construct could increase the mechanical stability of LSJ, reduce strain on the lumbosacral rod, and protect the S1-PS and sacrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although SPF indeed reinforces the construct stiffness, 12.0%–46.9% of implant failure rate has been reported by previous studies ( Park et al, 2021b ; Gao et al, 2021 ). To reduce the incidence of mechanical complications, multiple pelvic screws or multirod construct have been applied as an advanced SPF technique ( Uotani et al, 2021 ; Lee et al, 2022a ; Lee et al, 2022b ; Tang et al, 2022 ). The current study revealed that both multiple pelvic screws and multirod construct could increase the mechanical stability of LSJ, reduce strain on the lumbosacral rod, and protect the S1-PS and sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pseudarthrosis, postoperative residual sagittal and/or coronal malalignment are risk factors for implant failure following long spinal fusion for ASD ( Lee et al, 2022b ; Martin et al, 2022 ). For complex cases with preoperative several sagittal and coronal malalignment, three-column osteotomy (3-CO) and sequential correction techniques are usually needed ( Lau et al, 2021 ; Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations